Integrated Resonant Unit of Metasurfaces for Broadband Efficiency and Phase Manipulation. Issue 12 (18th April 2018) - Hsiao, Hui‐Hsin; Chen, Yu Han; Lin, Ren Jie; Wu, Pin Chieh; Wang, Shuming; Chen, Bo Han; Tsai, Din Ping
Abstract: Integrated‐resonant units (IRUs), incorporated with multiple resonators into one building block or one resonator with multiple modes, show a great capacity for achieving controllable smooth and linear phase dispersion as well as amplitude manipulation over a continuous and broad bandwidth. Based on an IRU library designed in the wavelength range of 400 to 667 nm, three achromatic deflectors showing constant steering angles of 9.5°, 19°, and 28°, respectively, are numerically validated. Achromatic metalenses with various numerical aperture (NA) values are further experimentally demonstrated, displaying an unvaried focal length throughout the bandwidth of 420–650 nm (≈50% bandwidth to the central wavelength). The focusing efficiency of the achromatic metalens with NA = 0.124 achieves 26.31%, 19.71%, and 20.37%, respectively, at wavelengths of 420, 550, and 650 nm. In addition, a multi‐nanorod IRU design is numerically optimized to achieve above 50% conversion efficiency from visible to near‐infrared (400–1400 nm). Such IRU design is then employed to construct a versatile polarization convertor, generating six different polarization states simultaneously upon one linear‐polarized illumination. The IRU approach with broadband control of amplitude and phase response provides an unprecedented platform in realizing multifunctional full‐color metadevices. Abstract : Integrated‐resonant units (IRUs), regarded as a building block consisting of multiple resonances, provide a great capacity for controlling phase dispersion as well as amplitude manipulation over a continuous and broad bandwidth. Here, by incorporating IRUs into metasurfaces, broadband and high efficiency achromatic beam deflectors, achromatic metalenses, and versatile polarization convertors are demonstrated.